Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2023)
A dataset containing 36215 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Ursus arctos Linnaeus, 1758" ] } The dataset includes 36215 records from 281 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0043163-230224095556074/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences